2018
DOI: 10.3389/fmicb.2018.01286
|View full text |Cite
|
Sign up to set email alerts
|

cpubi4 Is Essential for Development and Virulence in Chestnut Blight Fungus

Abstract: Ubiquitination plays key roles in eukaryotic growth, stress adaptation, and metabolic regulation. In our previous work, ubiquitin was found to be secreted in the hypovirus-infected strain of Cryphonectria parasitica, a phytopathogenic filamentous fungus responsible for the chestnut blight. Here we report the functional and molecular characterization of a polyubiquitin gene, cpubi4, in C. parasitica. The expression of cpubi4 was upregulated by the infection of a hypovirus. Deletion of cpubi4 resulted in abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…The polyubiquitin gene in fungi has been reported to be involved in stress responses such as heat stress [6,14,16,17]. Consistent with previous studies in yeast, C. albicans , and C. parasitica [6,17,18], the MrUBI4 mutant showed decreased resistance to high temperatures when compared to control strains. Previously, we found that the ubiquitin-proteasome pathway was significantly induced by heat stress in M. robertsii [28].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The polyubiquitin gene in fungi has been reported to be involved in stress responses such as heat stress [6,14,16,17]. Consistent with previous studies in yeast, C. albicans , and C. parasitica [6,17,18], the MrUBI4 mutant showed decreased resistance to high temperatures when compared to control strains. Previously, we found that the ubiquitin-proteasome pathway was significantly induced by heat stress in M. robertsii [28].…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, the conidiation assays showed that the conidia yield in ∆MrUBI4 was significantly reduced when compared to the control. Significantly reduced conidia yields were also observed in the polyubiquitin gene-deletion strains of M. oryzae [12] and cpubi4 (homolog gene of yeast UBI4 )-deletion strains of C. parasitica [18]. Accordingly, our qPCR results showed that the transcript levels of several conidiation-related genes, including brlA , abaA , wetA , and flbD , were significantly decreased in ∆MrUBI4 , thus indicating that MrUBI4 might be involved in the regulation of asexual sporulation.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Hsp70 functioned as a stress-related transcriptional co-activator is required for fungal virulence ( Weissman et al, 2020 ). Deletion of ubiquitin genes results in abnormal morphology, reduced sporulation, and attenuation of virulence ( Oh et al, 2012 ; Chen et al, 2018 ). SOD contributes to the growth and survival under conditions of oxidative stress ( Poli et al, 2004 ), and the antioxidant function of Cu SOD has been reported to be critical for the pathogenesis of fungi ( Narasipura et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%